Evaluation of the “Aviation Security” programme in Polish Air Force Academy - Czerski, Robert; Siczek, Dominika; Goniewicz, Krzysztof (Journal of Education, Health and Sport, 2019)
The article presents the opinion of students on undergraduate majoring in “Aviation Security” in Polish Air Force Academy. The aim of the study was to describe the training and propose changes in the educational process of students for the security. The article presents the aims and tasks of public education for the security of the State and analysis of the results that have been obtained on the basis of a questionnaire. The result of the research of the proposed changes might be to introduce students in the education process for the security of the state, to increase the efficiency of the process. presented she stayed proposal of changes in the requirements for the education of students for the security of the state and in the program and plan of full-time studies of the first degree in “Aviation Security” in Polish Air Force Academy